Chronic Smoking: Impact on Implant Survivorship Following Posterior Fusion Surgery in Degenerative Cervical Spine Disease. (16th November 2020) - Fatima, Nida; Shin, John H
Abstract: INTRODUCTION: With a substantial increase in the prevalence of smoking and attributable disease burden over time, it is imperative to understand its impact on the implants following spinal surgeries. METHODS: A retrospective chart review of consecutive patients presented with DCSD at an academic tertiary care hospital was carried out from 2009–2019. Kaplan-Meier analysis using Log-Rank test was used to determine differences between survivorship endpoints between smokers and non-smokers. Furthermore, Multivariate Cox regression model was used to determine the estimated hazards risk (HR) reading the endpoint of revision for mechanical failure. RESULTS: Among 199 patients included in our cohort, 59 patients (29.6%) were smokers and 140 patients (70.4%) were non-smokers. The patients who smoked at the time of surgery were more prone to hardware failure ( P  = .003) and eventually revision surgery ( P  = .001). The overall estimated survivorship for the spinal implants was 64.3 months (95%CI: 53.5-75.1 months) among smokers compared to the 118.4 months (95%CI: 111.7-125.0 months) for non-smokers ( P  = .001). Multivariate Cox regression analysis showed that smokers had a 9.3- folds (HR: 9.31, 95%CI: 1.82-47.7, P  = .007) higher risk than did non-smokers with regards to the endpoint of revision surgery following mechanical failure. CONCLUSION: Our study suggests that smoking is attributable risk factor for long-term implant survivorship following posterior fusion surgery in DCSD.